Technological Advancement and the Evolving Gender Identities: A Focus on the Level of Female Economic Participation in Sub-Saharan Africa - Uchenna Efobi; Belmondo Tanankem; Simplice Asongu (African Governance and Development Institute (AGDI), 2016)
This study investigates how technological advancement improves gender identity by means of female economic participation in a panel 48 African countries for the period 1990-2014. Two indicators are used to measure female economic participation, namely, the: female labour force participation and employment rates. Technological advancement is measured with three main indicators, notably: internet penetration, mobile phone penetration and fixed broad band subscriptions. The empirical evidence is based on Ordinary Least Squares, Fixed Effects and System Generalized Method of Moments regressions. The findings show that improvement in technology increases female economic participation with the following consistent order of increasing magnitude: mobile phone penetration; internet penetration and fixed broad band subscriptions. The findings are robust to the control for: countries' levels in economic development; the use of contemporary technology advancement indicators; internal conflicts and political stability; the level of social globalization and the use of alternative instruments. Policy implications are discussed.
Keywords: G20; I10; I32; O40; O55; 330; Technology; Inclusive development; Africa